Հայոց «Սասնայ ծռեր» դիցավէպի մի դրուագիժամանակի որոշման փորձ աստղագիտական իրողութիւնների միջոցով - Բրուտեան, Գրիգոր (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье предпринята попытка астрономическим путем оценить время создания армянского эпоса «Сасна црер». С точки зрения астрономии изучен эпизод, в котором Цовинар упоминает яркую звезду в качестве ночного проводника, отправляя своих сыновей в Армению. Основываясь на самопровозглашении представителей Дома Сасуна как «хачапашт» (поклоняющиеся кресту, крестопоклонники) и ношения знака креста на правом руке, данная путеводи- тельная звезда отождествляется с созвездием Лебедя (древнеармянский Ангх — Гриф), которое изображает очертание креста на северном небосклоне. Далее вычисляется, когда главная звезда Лебедя — Денеб, — была ближе всего к Северному полюсу. Получено, что это имело место 17 500 лет назад. Это-же время было принято, как время создания вышеупомянутого эпизода эпоса. An attempt is made to determine the time of the creation of the Armenian epic “Daredevils of Sassoon” through astronomical realities. From the point of view of astronomy, an episode has been studied, in which Tsovinar speaks of a bright star as a night guide, sending his sons from Mesopotamia to Armenia. As the representatives of the House of Sassoon considered themselves worshipers of cross and used to wear the sign of the cross on their right hands, this guiding star is identified with the constellation of Cygnus (ancient Armenian Vulture), which has the outline of a cross in the northern sky. Then calculations are made about the time, when Cygnus’ main star, Deneb, was the closest to the North Pole, according to which it took place 17 500 years ago. Thus, that very period is considered to be the time of the creation of the above-mentioned episode of the epic.
Keywords: Astronomical realities; Armenian folklore; Literature